The rooster crows : a book of American rhymes and jingles - Petersham, Maud Fuller, 1890-1971.; Petersham, Miska, 1888-1960. (New York : Aladdin Books ; London : Collier Macmillan, 1987)
A collection of traditional American nursery rhymes, finger games, skipping rhymes, jingles, and counting-out rhymes.
Library Journal
Caldecott 1946 Medal Winner
Horn Book
3.4
K-3
Keywords: Nursery rhymes, American; Children's poetry, American; Nursery rhymes; American poetry; Nursery rhymes; American poetry